Humor, Hikmah, dan Humanisme : Strategi Pembaharuan Islam dalam Pemikiran Gus Dur dan Gus Baha - Ade Kosasi; Sholahuddin Al-Ayubi; Andi Rosa (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This article examines humor, pesantren wisdom, and humanism as strategies of da'wah and Islamic reform employed by Abdurrahman Wahid and Ahmad Bahauddin Nursalim in responding to religious challenges, tolerance, and modernity. Using an intellectual history approach and the study of contemporary Islamic thought, this analysis demonstrates that both figures did not merely use humor as a rhetorical ornament, but rather as an alternative epistemology rooted in the scholarly traditions of pesantren and universal human values. Gus Dur developed a theological humanism that places human beings at the center of religious discourse, while Gus Baha employs scholastic humor grounded in fiqh and classical Qur’anic exegesis to deconstruct religious rigidity. The novelty of this article’s argument lies in the thesis that both figures collectively shaped what may be called a “humanistic pesantren paradigm”: a model of Indonesian Islamic intellectualism that transcends the dichotomy between traditionalism and modernism and offers an alternative to both sectarianism and secularism. The article concludes that humor and wisdom within their traditions are not merely styles of communication, but theological and ethical instruments affirming that Islam is a religion that celebrates reason, human dignity, and diversity.